Religious situation in Tuva: problems, directions and prospects (based on the materials of Western studies of the XXI century) - Izluchenko, Tatiana V.; Gergilev, Denis N.; Mamysheva, Elena P. (The New Research of Tuva, 2025)
The article presents the author's classification of works by Western researchers published in the early 21st century that focus on the religious situation in post-Soviet Tuva. The analysis has made it possible to identify established trends in the study of the diversity of religious experiences among the local population. Shamanic practices consistently attract scientific research interest, despite the presence of religious organizations in the region that belong to various religious traditions. The modern institutionalization of shamanism has highlighted the need to study the transformation of the religious life of Tuvans, the interaction between shamans and Buddhist clergy.The authors have identified and characterized the following research directions. In overview studies by F. Walters, E. Poppe, and B. Donahoe, the features of Tuva’s religious landscape, trends in the development of local beliefs and Tibetan Buddhism, and their transformation in post-Soviet realities are examined. In specialized studies on shamanism (E. Friedman, C. Humphrey, G. Lindquist, K. Zorbas), the influence of pre-Soviet spiritual elements on the revival of shamanic practices is analyzed. Other works (P. Bramwell, T. Levin, K. Pegg) highlight the ethnomusical component of shamanism and local chants (folklore), emphasizing their animistic nature and the interaction of Tuvans with the surrounding world. Particular attention is given to cognitive studies (K. Van Deusen, B. Purzycki, C. Stephanoff, T. Michael, M. Stelmazik, B. Christerson), which explore the formation of the specificity of local religious consciousness, ontological representations, and the role of the shaman as a social actor who communicates with spirits and ensures social order. Studies on shamanic-Buddhist synthesis are represented by the works of D. Harrison, K. Pimenova, and A. Olschlegel, who attempt to identify the common and unique aspects of the religious syncretism between shamanism and Buddhism.
Keywords: Tuva; Tuvans; post-Soviet Tuva; religious situation; shamanism; Buddhism; history of religion